2004
DOI: 10.1002/chem.200400656
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between the Spin Distribution and the Magnetic Ground State for a Triaminoxyl Substituted Triphenylphosphine Oxide Derivative

Abstract: The magnetic interaction and spin transfer via phosphorus have been investigated for the tri-tert-butylaminoxyl para-substituted triphenylphosphine oxide. For this radical unit, the conjugation existing between the pi* orbital of the NO group and the phenyl pi orbitals leads to an efficient delocalization of the spin from the radical to the neighboring aromatic ring. This has been confirmed by using fluid solution high-resolution EPR and solid state MAS NMR spectroscopy. The spin densities located on the atoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…1,2 Since most studies are limited to the magnetic ground state, synthetic efforts are currently devoted to the design of high-spin compounds, in which an appropriate topology gives rise to ferromagnetic interactions between the spin bearing units. [3][4][5] Therefore, topologies expected to allow antiferromagnetic interactions, yielding a singlet or low spin ground state, have been generally discredited. The recent observation, for purely organic pconjugated diradicals, of photo-excited quintet (S = 2) states starting from singlet ground state has relaunched the interest in designing systems with the ''wrong'' topology.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Since most studies are limited to the magnetic ground state, synthetic efforts are currently devoted to the design of high-spin compounds, in which an appropriate topology gives rise to ferromagnetic interactions between the spin bearing units. [3][4][5] Therefore, topologies expected to allow antiferromagnetic interactions, yielding a singlet or low spin ground state, have been generally discredited. The recent observation, for purely organic pconjugated diradicals, of photo-excited quintet (S = 2) states starting from singlet ground state has relaunched the interest in designing systems with the ''wrong'' topology.…”
Section: Introductionmentioning
confidence: 99%
“…Their schemes were found to be consistent with those expected for ferromagnetic interactions, however, their actual strengths were found to be too weak to be detectable by magnetic susceptibility measurements . NMR and EPR studies of other, more complex situations have been reported as well …”
Section: Spectroscopy Of Solid Bi‐ and Oligo‐radical Systemsmentioning
confidence: 69%
“…1b. However, since both nitrones and nitroxides have an N–O length of about 1.3 Å, 16,19,37,48–85 the bond length between the N and neighbouring sp 2 carbon atoms is important to determine the electron state of the N–O site. In fact, there is a difference in the N–C sp 2 length; the average lengths for nitrones are 1.31 Å (N–O: 1.29 Å), 48–53 those for aryl tert -butyl nitroxides are 1.43 Å (N–O: 1.29 Å), 16,19,37,45,54–71 and those for 10-oxy-9(10 H )acridines are 1.41 Å (N–O: 1.29 Å).…”
Section: Resultsmentioning
confidence: 99%